High cellulolytic activities in filamentous fungi isolated from an extreme oligotrophic subterranean environment (Catao cave) in Brazil - De Paula, Caio C. P.; Montoya, Quimi [UNESP]; Meirelles, Lucas A. [UNESP]; Farinas, Cristiane S.; Rodrigues, Andre [UNESP]; Seleghim, Mirna H. R. (Acad Brasileira De Ciencias, 2019)
Isolation and screening of new fungal strains from extreme and understudied environments. such as caves, is a promising approach to find higher yields enzyme producers. Cellulolytic fungal strains isolated from a Brazilian cave were evaluated for their enzymatic production after submerged (SmF) and solid-state fermentation (SSF). After SmF, three strains were selected for their high enzymatic activities: Aspergillus ustus for endoglucanase (4.76 U/mg), Talaromyces bruneus for beta-glucosidase (11.71 U/mg) and Aspergillus sp. (CBMAI 1926) for total cellulase (1.70 U/mg). After SSF, these strains, showed better yields compared to the reference strain Aspergillus niger 3T5B8. Aspergillus sp. (CBMAI 1926) stood out as a new species that expressed activity of total cellulases (0.10 U/mg) and low protein concentration (0.44 mg/mL). In conclusion, these isolated strains have a more efficient and promising cellulolytic enzyme complex that can be used in fermentation and saccharification processes with a lower protein concentration and a higher enzymatic activity than the reference strain. Therefore, beside the new genetic material characterized, our study highlights the benefits of cave extreme environments exploitation to find new potentially valuable strains.
Keywords: cellulases; fungu's cave; solid state fermentation; submerged fermentation; subterranean environment